Oncofertility in pediatric patients: current perspectives - Marques, Rafael; Oura, Maria; Dionísio, Rita; Rodrigues, Catarina; Lorenzo, Joana (Contemporary Oncology/Współczesna Onkologia, 2022)
Cancer treatments may affect fertility in different ways. Oncofertility, i.e. the study of interactions between cancer, anti-cancer therapy, fertility, and reproductive health, is an emerging field that addresses cancer patients’ concerns regarding their future reproductive ability. As the number of cancer survivors increases, fertility preservation is becoming an important quality of life issue for many survivors of childhood cancer. There is a wide array of fertility preservation options according to gender and pubertal status, and shared decisions must take place at the time of diagnosis. Even though there might be several barriers that can negatively affect this process, the presence of a dedicated fertility preservation team may help overcome them. In this article, the authors aim to characterize what oncofertility is, the effects of cancer and its treatments on the fertility potential of pediatric patients and also on their mental health. Another goal is to expose the different fertility preservation therapeutic options and potential barriers.